Identification Analysis of Influencing Factors of Construction Business Success: A Case of the Malaysian Construction Industry - Abd Hamid, Zahidy; Noor Azlinna, Azizan; Sorooshian, Shahryar (Global Research & Development Services, 2016)
Although the construction industry is one of the important components of the nation’s economic development, nevertheless, a nation can only fully benefited from the construction activities if it has an efficient and effective construction industry. Against the traditional conceptions of success in the construction industry, this paper attempts to explore the factors that influence the success of the construction enterprise from the viewpoint of an entrepreneurship perspective. In this regard, the importance factors to the construction enterprise success were determined based on the entrepreneurship literature and experts’ opinions, and categorized into four dimension and eighteen factors. Then, the Decision Making Trial and Evaluation Laboratory (DEMATEL) technique was applied to explore the causal relationships among the factors. The results revealed that three factors were of great importance to the success of the construction enterprise, namely ‘Business and Management Competencies’, ‘Technical Competencies’, and ‘Technological Competencies’. It is advised that if the construction enterprises desire to obtain high potential in business success, they should focus on these factors by enhancing their practice in this areas.